2016
DOI: 10.1007/s10936-016-9470-y
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pinyin Input Experience on the Link Between Semantic and Phonology of Chinese Character in Digital Writing

Abstract: With the development of ICT, digital writing is becoming much more common in people's life. Differently from keyboarding alphabets directly to input English words, keyboarding Chinese character is always through typing phonetic alphabets and then identify the glyph provided by Pinyin input-method software while in this process which do not need users to produce orthography spelling, thus it is different from traditional written language production model based on handwriting process. Much of the research in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…With advances in technology, typing and handwriting have become equally important in school education ( Mangen and Balsvik, 2016 ; Amez and Baert, 2020 ; Verhoeven et al, 2020 ). Previous research has found that handwriting enhances orthographic awareness while typing enhances phonological awareness and phonetic-semantic mapping in Chinese learning ( Chen et al, 2016a , b ; Guan and Wang, 2017 ). In addition, a review of case studies on handwriting and typing impairment found that both can serve as important indicators of stroke ( Sharma et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…With advances in technology, typing and handwriting have become equally important in school education ( Mangen and Balsvik, 2016 ; Amez and Baert, 2020 ; Verhoeven et al, 2020 ). Previous research has found that handwriting enhances orthographic awareness while typing enhances phonological awareness and phonetic-semantic mapping in Chinese learning ( Chen et al, 2016a , b ; Guan and Wang, 2017 ). In addition, a review of case studies on handwriting and typing impairment found that both can serve as important indicators of stroke ( Sharma et al, 2019 ).…”
Section: Discussionmentioning
confidence: 97%
“…Although some studies have found that excessive use of typing may lead to a decline in handwriting speed and fluency and deterioration of handwriting motor skills ( Sülzenbrück et al, 2011 ), typing does have tremendous advantages in other aspects. For example, typing is much faster than writing, and the content of typing is more recognizable ( Chen et al, 2016a , b ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have supported the benefits of using typing for character learning. The Pinyin input experience strengthens the semantic-phonology linkage in learners' mental lexicon and improves character recognition, even for advanced learners (Chen et al, 2017). In addition, typing on computers helps learners to write and express their ideas because their vocabulary is not limited by their inability to write certain Chinese characters (Zhang and Min, 2019).…”
Section: Teacher Instruction In L2 Chinese Character Teachingmentioning
confidence: 97%
“…Therefore, children need both phonetics and written morphology to write Chinese characters. Pinyin input involves both the process of speech production and the recognition of Chinese characters ( Chen et al, 2017 ) by first typing Pinyin based on semantics and then selecting the desired character from alternative homophones. Numerous studies have found that pinyin input experience facilitates both phonological and orthographic processing, and that high proficiency in Pinyin input is beneficial for character recognition and further improves literacy performance.…”
Section: Literature Reviewmentioning
confidence: 99%